DAMPAK STRATEGI EWOM DI TIKTOK DALAM PENINGKATAN MINAT BELI PRODUK SKINTIFIC - Made Sri Oriana Laksmi,; Ni Putu Yunita Anggreswari,; Anak Agung Mia Intentilia,; Putu Dyah Permata Korry, (Journal of Innovation Research and Knowledge, 2025)
The current beauty industry is highly advanced and modern, both internationally and in Indonesia. This technological advancement has had a significant impact on the industry. One beauty brand that has embraced modern technological advancements is Skintific. This study aims to analyze the impact of electronic word-of-mouth (eWOM) strategies, through content published on TikTok, on increasing purchase interest in Skintific products. Skintific utilizes eWOM strategies through TikTok, which strengthen consumer perceptions through user testimonials regarding the quality of Skintific products. The eWOM strategy is highly effective in influencing consumer perceptions and building trust through interactive interactions in comments, duets, or the stitch feature provided by TikTok, which will have a positive effect, namely, content going viral and being effectively conveyed to the entire audience. The author employed descriptive qualitative research and data collection through interviews. The results indicate that the eWOM strategy can have a positive and significant impact on increasing purchase interest in Skintific beauty products. Skintific’s eWOM strategy through Tiktok significantly increased consumer purchase interest and facilitated consumer education about Skintific products.